2016
DOI: 10.1002/2016gl070511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrate nucleation mechanisms and capillarity on permeability reduction in granular media

Abstract: A model for water permeability reduction in hydrate‐bearing sediments is presented by considering capillary effect in hydrate nucleation. Both grain‐coating and pore‐filling cases are considered. The model is developed from a series of lattice Boltzmann flow simulations. Results show that the permeability decreases quasi‐linearly with increasing hydrate saturation during grain‐coating nucleation and that the permeability tends to be higher than predicted by previous analytical models, in which capillarity is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 32 publications
(38 reference statements)
3
66
1
Order By: Relevance
“…Recent micro-CT work by Lei et al (2018) has directly observed hydrate formation in pores and associated changes in salinity. Microfluidics (e.g., Kang et al, 2016;Martinez de Baños et al, 2015) and micro-Raman (e.g., Davies et al, 2010;Prasad et al, 2009) experiments have visually investigated and analyzed the dynamic processes of hydrate formation and dissociation. We also know that Oswald ripening not only changes the morphology of methane hydrate (e.g., Katsuki et al, 2007) but also redistributes methane hydrate in pores and leads to patchy distribution (e.g., Dai et al, 2012;Rees, Kneafsey et al, 2011;You, Kneafsey, et al, 2015).…”
Section: Future Studies To Illuminate How Hydrate Systems Formmentioning
confidence: 99%
“…Recent micro-CT work by Lei et al (2018) has directly observed hydrate formation in pores and associated changes in salinity. Microfluidics (e.g., Kang et al, 2016;Martinez de Baños et al, 2015) and micro-Raman (e.g., Davies et al, 2010;Prasad et al, 2009) experiments have visually investigated and analyzed the dynamic processes of hydrate formation and dissociation. We also know that Oswald ripening not only changes the morphology of methane hydrate (e.g., Katsuki et al, 2007) but also redistributes methane hydrate in pores and leads to patchy distribution (e.g., Dai et al, 2012;Rees, Kneafsey et al, 2011;You, Kneafsey, et al, 2015).…”
Section: Future Studies To Illuminate How Hydrate Systems Formmentioning
confidence: 99%
“…48,49 The IFT values combined with CA are important for the measurement of relative permeability and the water retention curve. [50][51][52][53] The surface de-wetting phenomenon by CO 2 has been reported in the literature. Chiquet et al 54 and Kim et al 55 reported that the de-wetting phenomenon is a result of the low pH of water saturated with CO 2 .…”
Section: Contact Anglementioning
confidence: 95%
“…In the studies of CO 2 invasion into porous media, the effect of IFT is considered important; however, the effect of CA is overlooked . The IFT values combined with CA are important for the measurement of relative permeability and the water retention curve …”
Section: Background – Literature Reviewmentioning
confidence: 99%
“…Capillary pressure also plays an important role in percolation properties of multiphase flow in hydrate‐bearing medium, where capillary pressure versus water saturation curve can be used to assess properties such as the degree of sorting and pore size distribution; a medium with uniform pore size distribution leads to a well‐sorted medium that is depicted by an elongated horizontal segment of the capillary pressure curve (Wang et al, ). It has been found that the presence of capillarity results in higher water permeability than when there is no capillarity for both grain‐coating and pore‐filling hydrates (Kang et al, ), but the mechanisms that reduce permeability in presence of hydrates (channel blocking and pore size reduction) are also alleviated a little (Kang et al, ) in the presence of capillarity. The formation of hydrates also affects the capillary pressure of the hydrate‐bearing sediments, such that with the increase in hydrate saturation, the average pore size decreases while the distribution of pore size becomes wider (Mahabadi, Dai, et al, ), which leads to an increase in air entry value of capillary pressure.…”
Section: Modelmentioning
confidence: 99%
“…As an alternative to experiments, some researchers rely on fitting empirical relative permeability models (Joseph et al, 2016) to pore network modeling results (Kang et al, 2016;Katagiri et al, 2017;Mahabadi & Jang, 2014;Mahabadi, Dai, et al, 2016, Mahabadi, Zheng et al, 2016Wang et al, 2015), which, although useful, is limited by the lack of mechanistic models to describe petrophysical properties in addition to the computational expense required in developing a new pore network model for each scenario. The empirical relative permeability models used in pore network modeling, particle-based 3-D packs (Katagiri et al, 2016(Katagiri et al, , 2017, or otherwise (Yoneda et al, 2018) essentially involve fitting relative permeability curve separately for each hydrate saturation, which gives different model parameters for each hydrate saturation.…”
Section: Introductionmentioning
confidence: 99%